Pengaruh Kualitas Pelayanan, Harga, dan Fasilitas Terhadap Kepuasan Wisatawan di Wisata Bukit Sekipan Tawangmangu - Agung Suardi Sakaletuk; Dokman Marulitua Situmorang (Jurnal Minfo Polgan, 2026)
This study aims to examine the influence of service quality, price, and facilities on tourist satisfaction at Bukit Sekipan Tawangmangu Tourism. The sample size was 80 respondents. Data were collected through a five-point Likert-scale closed questionnaire that had undergone validity and reliability testing. Multiple linear regression analysis with the help of SPSS version 29 was used to test the partial and simultaneous effects at a significance level of 5%. The results showed that service quality had a positive and significant effect on tourist satisfaction. Price also had a positive and significant effect on tourist satisfaction and was proven to be the most dominant variable based on the Standardized Beta value of 0.467. Facilities had a positive and significant effect on tourist satisfaction. Simultaneously, service quality, price, and facilities had a positive and significant effect on tourist satisfaction, contributing 40.2% to the variation in tourist satisfaction. These findings imply that tourism managers need to improve service quality, ensure value for money, and develop facilities sustainably to increase tourist satisfaction. Further research is recommended to add other variables such as tourist attractions, destination image, and accessibility to a wider and more diverse population.